2004
DOI: 10.1210/jc.2002-021057
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in Patients with Reduced REM Sleep Duration: Two Randomized Controlled Trials

Abstract: Recent data suggest that melatonin may influence human physiology, including the sleep-wake cycle, in a time-dependent manner via the body's internal clock. Rapid-eye-movement (REM) sleep expression is strongly circadian modulated, and the impact of REM sleep on primary brain functions, metabolic processes, and immune system function has become increasingly clear over the past decade. In our study, we evaluated the effects of exogenous melatonin on disturbed REM sleep in humans. Fourteen consecutive outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
66
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 53 publications
3
66
0
7
Order By: Relevance
“…33 Furthermore, exogenous melatonin increases REM sleep duration in healthy controls 34 and in patients with abnormally lowered REM sleep. 35 The absence of circulating levels of melatonin in tetraplegia patients is associated with increased latency to REM sleep. 36 Based on these previous studies, it is hypothesized that the observed trend toward lower REM sleep in the TBI group is related to the reduced levels of melatonin, the attenuated melatonin levels possi- Abbreviations: SWS ϭ slow wave sleep; TBI ϭ traumatic brain injury; WASO ϭ wake after sleep onset.…”
mentioning
confidence: 99%
“…33 Furthermore, exogenous melatonin increases REM sleep duration in healthy controls 34 and in patients with abnormally lowered REM sleep. 35 The absence of circulating levels of melatonin in tetraplegia patients is associated with increased latency to REM sleep. 36 Based on these previous studies, it is hypothesized that the observed trend toward lower REM sleep in the TBI group is related to the reduced levels of melatonin, the attenuated melatonin levels possi- Abbreviations: SWS ϭ slow wave sleep; TBI ϭ traumatic brain injury; WASO ϭ wake after sleep onset.…”
mentioning
confidence: 99%
“…24,25 For example, nocturnal administration of melatonin to subjects with either suppressed or incorrect timing of the nocturnal melatonin peak 26 improves sleep quality and especially REM sleep duration. 27 Nocturnal melatonin suppression in intensive care unit patients and postoperative patients has been described, 28,29 but the effect of opioids on nocturnal secretion of melatonin has not been described. This study tests the hypothesis that an overnight constant infusion of remifentanil inhibits both nocturnal REM sleep and melatonin secretion in normal humans, and that administration of exogenous melatonin during opioid administration will ameliorate the opioid-induced sleep disturbance.…”
mentioning
confidence: 99%
“…The activation of type 1 occurs by inducing a receptor-suppressed neuronal firing rate in CNS, while type 2 induces circadian phase shift [Ebadi, 1992;Geoffriau et al, 1998;Starc, 1998;Dubocovich et al, 2003;Murphy and Delanty, 2007]. Some studies do not confirm the influence of melatonin on the duration of sleep [Hughes et al, 1998], while others support the effect of melatonin on the duration and quality of REM sleep because they assume that it directly influences either the cholinergic activity in REM sleep, or, indirectly, the elimination of serotonergic or aminergic activity [Jones, 1991;Kunz et al, 2004]. There are a number of other factors that could affect sleep, including adenosine in the brain and neuroendocrine dysregulation, but mostly in primary insomnia [Rodenbeck and Hajak, 2001;Mignot et al, 2002].…”
Section: Mercurialism and Sleep Disordersmentioning
confidence: 99%